Peran guru dalam mengatasi masalah siswa yang tidak disiplin dalam belajar - Yatimi, Muh Asrul (Maliki Interdisciplinary Journal, 2023)
A B S T R A C T The teacher plays an important role in improving the quality of students. Especially in overcoming problems in students who are not disciplined in learning. The aim is to find out the teacher's role in overcoming the problems of students who are not disciplined in their learning. The method used is qualitative. The results are the teacher's role in this problem. namely, providing guidance, direction, and advice that can increase student enthusiasm for learning. The conclusion is the role of the teacher in overcoming problems in students who are not disciplined in learning, namely: providing guidance, direction, advice, understanding, and alleviation of students both through school programs, communication open to children and parents of children, and always hugging and encouraging children.